2008
DOI: 10.1590/s0104-66322008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Mass transfer inside oblate spheroidal solids: modelling and simulation

Abstract: -A numerical solution of the unsteady diffusion equation describing mass transfer inside oblate spheroids, considering a constant diffusion coefficient and the convective boundary condition, is presented. The diffusion equation written in the oblate spheroidal coordinate system was used for a two-dimensional case. The finite-volume method was employed to discretize the basic equation. The linear equation set was solved iteratively using the Gauss-Seidel method. As applications, the effects of the Fourier numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
0
10
0
3
Order By: Relevance
“…Several studies have been reported in literature using a diffusion model to describe the physical process, and consider the geometric shape of the bodies as cylinder, sphere, or infinite slab [7][8][9][10][11]. Analytical and numerical solutions to predict heat and mass diffusion in porous bodies are also reported for prolate and oblate spheroids [12,13], as well as parallelepipeds [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported in literature using a diffusion model to describe the physical process, and consider the geometric shape of the bodies as cylinder, sphere, or infinite slab [7][8][9][10][11]. Analytical and numerical solutions to predict heat and mass diffusion in porous bodies are also reported for prolate and oblate spheroids [12,13], as well as parallelepipeds [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, in many situations the shape of the particles immersed in a fluid or porous media is not perfectly spherical, and may be classified as prolate or oblate spheroids. Numerical and analytical solutions of the diffusion equation for prolate spheroids have been reported by Coutelieris et al (2004), Lima et al (2002), Coutelieris et al (1995), etc., and for oblate spheroids by Carmo and Lima (2008), Coutelieris et al (1995), etc. Fluid flow along buried spheroidal surfaces is an important model situation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Se uma solução analítica for usada para descrever um processo de secagem, mais hipóteses simplificadoras são requeridas para que tal solução possa ser obtida. Dentre estas hipóteses, pode-se ressaltar volume e difusividade constantes, além de meio homogêneo e isotrópico (OLIVEIRA e LIMA, 2002;LIMA et al, 2004a;AMENDOLA e QUEIROZ, 2007;MELLADO, 2007;OLEK e WERES, 2007;CARMO e LIMA, 2008).…”
Section: Capítulounclassified
“…Entretanto, para uma descrição detalhada do transporte de água, modelos matemáticos devem ser usados. Vários modelos são reportados na literatura e, dentre esses, podem ser citados os modelos empíricos (GOUVEIA et al, 2002;BAINI e LANGRISH, 2007;GOYAL et al, 2007;MARTINAZZO et al, 2007), os modelos de difusão (OLIVEIRA e LIMA, 2002, LIMA et al, 2004aNASCIMENTO et al, 2005;AMENDOLA e QUEIROZ, 2007;CARMO e LIMA, 2008;BAINI e LANGRISH, 2008;SILVA et al, 2009d; SILVA, C., 2010) e o modelo de Darcy (PINHEIRO et al, 1998). O objetivo do uso desses modelos é correlacionar os dados experimentais da secagem a uma equação matemática que vai representar a cinética de secagem do produto.…”
Section: -Simulação Da Secagemunclassified
See 1 more Smart Citation